2008
DOI: 10.1016/j.jnn.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Non-nutritive suck parameters in preterm infants with RDS

Abstract: Objective-To characterize the integrity of non-nutritive suck (NNS) parameters among three groups of preterm infants ranging from normal to those with progressive degrees of respiratory distress syndrome (RDS).Study Design-NNS compression waveforms were sampled from 55 infants in the neonatal intensive care unit using a silicone pacifier electronically instrumented for intraluminal pressure. Seven select NNS parameters were measured at two different sessions, and statistically analyzed using a General Linear M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Thus the younger the GA, the longer these interventions are done and therefore feeding milestone delays are evident. These findings support that failed opportunities or motor restriction may delay feeding goals 23-26. On the other hand, most premature infants attain maximal oral feedings by the median age of 35-37 wks PMA; thus, identifying maturity of this skill at this PMA as a real biologic marker may offer realistic expectations.…”
Section: Discussionmentioning
confidence: 53%
“…Thus the younger the GA, the longer these interventions are done and therefore feeding milestone delays are evident. These findings support that failed opportunities or motor restriction may delay feeding goals 23-26. On the other hand, most premature infants attain maximal oral feedings by the median age of 35-37 wks PMA; thus, identifying maturity of this skill at this PMA as a real biologic marker may offer realistic expectations.…”
Section: Discussionmentioning
confidence: 53%
“…[1][2][3] Many of these premature infants have endured an extensive course of respiratory support (oxygen therapy, positive pressure ventilation and/or nasal cannulation) due to the immaturity of the lungs and respiratory disease. As pulmonary function improves, these infants often manifest oromotor dyscoordination, absent or weak non-nutritive suck (NNS), 4,5 poor airway protection, dysphagia 6 and poor state control. 7 Some investigators contend that the invasiveness of lengthy intubation and oxygen supplementation procedures associated with prematurity cost the baby precious sensory and motor experiences during a critical period of brain development for oromotor pattern generation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it would have been ideal to use them in combination with other rhythms of the newborn’s nervous systems. For example, the same statistical platform that we used here could have been applied to time series of waveforms from respiratory or feeding (sucking) rhythms (11, 12, 26) easy to harness in the NICU or in typically newborn infant wards (27). Feeding and non-feeding sucking patterns require precise motor control from orofacial structures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that newborn infants naturally entrain their bodily rhythms with those of the adult’s speech (9); an ability that is compromised in individuals that go on to receive a diagnosis of a neurodevelopmental disorder (10). Related perinatal research points at the intertwined relations between respiration, sucking patterns, and speech (11, 12). Such work highlights the importance of well-functioning orofacial sensory–motor structures to scaffold the production of motoric rhythms (11, 13), the later emergence of spoken language abilities, and their potential role as precursors of other cognitive and social capacities.…”
Section: Introductionmentioning
confidence: 99%